Analisis Pengaruh Bahan Terhadap Faktor Keamanan Footstep Sepeda Motor Menggunakan Metode Elemen Hingga - Prasetyo, Januar Teguh; Karohika,, I Made Gatot; Parwata, I Made (Teknik Desain Mekanika; Vol 13 No 1 (2024): Januari 2024 : Teknik Desain Mekanika, 2024)
Abstract Motorcycle production in Indonesia in 2021 is 5,057,516 units and there will be an increase to 5,221,470 units in 2022 based on data from the Indonesian Motorcycle Industry Association. One component of a motorcycle that acts as a foothold for the rider and passenger of a motorcycle is the footstep, besides that the footstep also plays a role in maintaining stability when driving. In general, the basic materials for making footstep can vary from cast iron, aluminum to titanium. Therefore, this study aims to determine the effect of the footstep constituent materials on the value of the safety factor by simulating using engineering applications. This study uses a static structural simulation with a loading of 800N which is taken from the weight of the motorbike rider. As well as the materials used are 1020 carbon steel, 6061 aluminum alloy, and titanium alloy found in the ansys application. This simulation aims to determine the total deformation, equivalent stress, and safety factor. Based on the simulation results, the highest safety factor value is in the footstep made of aluminum alloy 6061, which is 12.749. This is influenced by the differences in the yield stress of each material and it can be concluded that the footstep made from titanium alloy has the highest safety factor compared to other materials. Keywords: Von mises,finite element methode,footstep